2021
DOI: 10.1093/cid/ciab536
|View full text |Cite|
|
Sign up to set email alerts
|

Improved Survival Among Hospitalized Patients With Coronavirus Disease 2019 (COVID-19) Treated With Remdesivir and Dexamethasone. A Nationwide Population-Based Cohort Study

Abstract: Background There is limited data on outcomes of moderate to severe Coronavirus disease 2019 (COVID-19) among patients treated with remdesivir and dexamethasone in a real-world setting. Objective To compare the effectiveness of standard of care (SOC) alone vs SOC plus remdesivir and dexamethasone. Methods Two population-based nationwide cohorts of individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 13 publications
3
66
0
2
Order By: Relevance
“…The combination may treat the viral infection and dampen the potentially injurious inflammatory response that is a consequence of the infection. However, the data on clinical outcomes for patients who received this combination are currently limited [ 50 ]. If dexamethasone isn't accessible, other corticosteroids like prednisone, methylprednisolone or hydrocortisone can be used in place of it.…”
Section: Main Textmentioning
confidence: 99%
“…The combination may treat the viral infection and dampen the potentially injurious inflammatory response that is a consequence of the infection. However, the data on clinical outcomes for patients who received this combination are currently limited [ 50 ]. If dexamethasone isn't accessible, other corticosteroids like prednisone, methylprednisolone or hydrocortisone can be used in place of it.…”
Section: Main Textmentioning
confidence: 99%
“…The hyperactivated and dysregulated immune system in critical cases necessitates anti-inflammatory immunotherapy [ 3 ]. Recently, several clinical studies demonstrated that the FDA-approved glucocorticoid drug dexamethasone is able to reduce disease severity and mortality in hospitalized human patients with SARS-CoV-2 infection [ 4 , 5 ]. In contrast to newly developed drugs, dexamethasone has unique advantages, including being inexpensive and widely available and having 60 years of safety profiling [ 6 ].…”
mentioning
confidence: 99%
“…Similarly, including the pandemic week in which a patient had their FPT as a feature revealed that patients early rather than later in the pandemic, had a higher risk of dying. As our data covered both the first and second pandemic wave in Denmark, this finding likely reflects that our model captured improvements in the clinical management of patients throughout the pandemic 54 .…”
Section: Discussionmentioning
confidence: 86%